Growth from International Capital Flows : The Role of Volatility Regimes - Murshid, Antu (IMF Working Papers; Working Paper, 2011)
Recent commentary has downplayed the growth dividend from international financial integration, highlighting the possibly negative correlation between capital inflows and long-run growth. This paper presents new evidence consistent with standard economic theory and a more benign interpretation of cross-border private capital flows. The key observation is that a country's growth volatility changes over time. With volatility below a threshold, an inflow of foreign capital has promoted growth. However, during periods of volatile growth, more flows have been associated with slower growth. Volatility levels and changes reflect an interaction of domestic production and institutional structures with global factors.